2014
DOI: 10.21273/hortsci.49.5.637
|View full text |Cite
|
Sign up to set email alerts
|

Groundcover Management and Nutrient Source Effects on Soil Carbon and Nitrogen Sequestration in an Organically Managed Apple Orchard in the Ozark Highlands

Abstract: Orchards established on weathered, acidic mineral soils in the Ozark Highlands must be managed to meet tree nutritional requirements. However, a common characteristic of Ozark Highland soils is a relatively low soil organic matter (SOM) concentration, a condition that can have detrimental effects on orchard productivity. Organic orchard management poses specific challenges to managing competitive under-tree vegetation and supplying appropriate supplemental nutrition to maintain tree growth and cropping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Previously, we have reported that SOM in the top 10 cm increased over time in all GMS with the largest increase occurring in the green compost treatment (Mays et al, 2014). Furthermore, despite initial uniformity in 2006 before planting where SOM concentration averaged 1.5% across all treatments, by 2012, SOM concentration differed among nutrient sources within GMS (Mays et al, 2014).…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…Previously, we have reported that SOM in the top 10 cm increased over time in all GMS with the largest increase occurring in the green compost treatment (Mays et al, 2014). Furthermore, despite initial uniformity in 2006 before planting where SOM concentration averaged 1.5% across all treatments, by 2012, SOM concentration differed among nutrient sources within GMS (Mays et al, 2014).…”
Section: Resultsmentioning
confidence: 71%
“…Soil organic matter has often used as a soil quality indicator (Fliebach et al, 2006;Granatstein and Mullinix, 2008;Gregorich et al, 1994;Karlen et al, 1992;Loveland and Webb, 2003;Merwin et al, 1994Merwin et al, , 1995, and changes in SOM have been linked to changes in other soil properties and processes. The near-surface SOM, total C, and total nitrogen (N) concentrations and contents, C:N ratios, and BD did not differ (P > 0.05) among GMS-nutrient source treatment combinations at the initiation of the study (Mays, 2013) indicating that soil conditions were as uniform throughout the study area as could reasonably be expected at the time of organic orchard establishment. Therefore, it was reasonably assumed that differences observed among treatments over the subsequent years were the result of the treatments rather than inherent differences.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations